Association Between Suicide and Drinking Habits in Adolescents - Lee, Ji Won; Kim, Bong-Jo; Lee, Cheol-Soon; Cha, Boseok; Lee, So-Jin; Lee, Dongyun; Seo, Jiyeong; Lee, Young-Ji; Lee, Youn-Jung; Lim, Eunji; Choi, Jae-Won (Journal of korean Academy of Child and Adolescent Psychiatry, 2021)
Adolescent suicide is a serious social problem. Adolescent alcohol use is one of the most important risk factors for adolescent suicide. This study aimed to identify the relationship between drinking habits and suicide among Korean adolescents. Data from the 14th and 15th Korean Youth Risk Behavior Web-based Survey, conducted in 2018 and 2019, were used for analysis. Multiple logistic regression analysis was used to identify the relationship between drinking habits-including the age of drinking initiation, frequency of drinking, average drinking amount, frequency of drunkenness-and suicidal ideation, plans, and attempts. Even after adjusting for age, sex, school grade, academic achievement, socioeconomic status, depression, stress, and drinking habits, the frequencies of drinking and drunkenness increased the risk of suicide attempts. Suicide attempts were associated with the frequency of drinking in girls and middle school students, and with the frequency of drunkenness in boys and high school students. This study identified associations between drinking habits (the age of drinking initiation, frequency of drinking, average amount of drinking, frequency of drunkenness) and suicidal behavior in adolescents. Our findings suggest that to prevent adolescent suicide, it might be necessary to investigate drinking habits, including the frequencies of drinking and drunkenness. Moreover, considering the differences in sex and school grade, it is important to include the individual group characteristics when evaluating drinking habits.